2020
DOI: 10.1016/j.jcrc.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant anticardiolipin antibodies associated with COVID-19

Abstract: The novel coronavirus strain known as SARS-CoV-2 has rapidly spread around the world creating distinct challenges to the healthcare workforce. Coagulopathy contributing to significant morbidity in critically ill patients with SARS-CoV-2 has now been well documented. We discuss two cases selected from patients requiring critical care in April 2020 in New York City with a unique clinical course. Both cases reveal significant thrombotic events noted on imaging during their hospital course. Obtaining serial inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…Considering LA, any anti-cardiolipin and any anti-β2-GP1 antibodies, 8 (32%) patients had single APLa positivity, 13 (52%) had double positivity, 3 (12%) had triple positivity and only one (4%) was triple negative. Other case reports have also demonstrated that antiCL Abs are associated with thrombosis during COVID-19 infection ( 53 ).…”
Section: Can the Thromboembolic Diathesis During Some Cases Of Covmentioning
confidence: 90%
“…Considering LA, any anti-cardiolipin and any anti-β2-GP1 antibodies, 8 (32%) patients had single APLa positivity, 13 (52%) had double positivity, 3 (12%) had triple positivity and only one (4%) was triple negative. Other case reports have also demonstrated that antiCL Abs are associated with thrombosis during COVID-19 infection ( 53 ).…”
Section: Can the Thromboembolic Diathesis During Some Cases Of Covmentioning
confidence: 90%
“…9 In addition, it has been reported in some cases that COVID-19 patients may have positive antiphospholipid antibodies that may play a role in hypercoagulable state, as seen in our patient. 10,11 Venous thromboembolism including pulmonary embolism is the most common thrombotic manifestation of COVID-19. Kaminetzky et al 12 mentioned in his cohort study that 37.1% of the COVID-19 patients were positive for pulmonary embolism demonstrated by the computerized tomography of the pulmonary arteries (CTPA).…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80] There is a lack of literature on patients with known APS who go on to develop COVID-19 infection; however, multiple lines of evidence link COVID-19 with a hypercoagulable state and thrombosis, and numerous studies have assayed the co-occurrence of antiphospholipid antibodies. [81][82][83][84][85][86] There is evolving evidence for high thrombotic risk in patients with severe COVID-19 infection. A Dutch study of 184 intensive care patients with COVID-19 pneumonia found 31% of patients had thrombotic complications.…”
Section: Anti-phospholipid Syndrome and Covid-19mentioning
confidence: 99%
“…91 Other cases are reported of pulmonary emboli, ischaemic strokes, limb and digital ischaemia and deep vein thromboses in patients with positive antiphospholipid antibodies. 85,[92][93][94][95] A French study of 150 patients on an intensive care unit due to COVID-19 related ARDS found that 64/150 had clinically significant thrombotic events during ICU stay. 57 patients were tested for LAC (based on a prolonged aPTT at ICU admission or on having had a thrombotic event during ICU stay) and 50/57 were positive (87.7%).…”
Section: Anti-phospholipid Syndrome and Covid-19mentioning
confidence: 99%